The correlation between miR -34a-3p, miR -31, PLEK2 and the occurrence, development and prognosis of colorectal cancer - Bin, He; Mei, Han; Hui, Wang; Bing, Zheng (Cellular and Molecular Biology, 2022)
The current study aimed to explore the correlation between Mir-34A-3p, Mir-31, PLEK2 and the occurrence, development and prognosis of colorectal cancer. For this paper, 120 patients with colorectal cancer were selected as the study group, and their adjacent normal tissues were selected as the control group. The quantitative real-time PCR (QRT-PCR) method was used to detect miR-34a-3p and miR-31 in tissues, and the immunohistochemistry EnVision two-step method was used to detect PLEK2 positive expression. The expressions of miR -34a-3p, miR -31, and PLEK2 in colon cancer tissues and normal cancer tissues were compared, and the correlation between miR -34a-3p, miR -31, and PLEK2 and clinic-pathological characteristics of colorectal cancer patients were analyzed. The results showed that expression of miR -34a-3p, miR -31 and positive expression rate of PLEK2 in colorectal cancer tissues were higher than those in normal adjacent tissues (P<0.05). The expression of miR -34a-3p was related to tumor size, degree of tissue differentiation, lymph node metastasis and TNM stage (P < 0.05). The 3-year survival rate of miR -34a-3p with low expression was lower than miR -34a-3p with high expression, which was a protective factor affecting the poor prognosis of colorectal cancer (P < 0.05). The expression of miR -31 was related to tumor size and TNM stage. The 3-year survival rate of the group with high expression of miR -31 was lower than the group with low expression of miR -31, which was a risk factor affecting the poor prognosis of colorectal cancer (P < 0.05). PLEK2 positive expression was associated with lymph node metastasis, and the 3-year survival rate of the PLEK2 positive group was lower than the PLEK2 low expression group, which was a risk factor for poor prognosis of colorectal cancer (P < 0.05). In general, miR -34a-3p, miR -31, and PLEK2 are closely associated with the occurrence and development of colorectal cancer, and they are all influential factors affecting the prognosis of patients with colorectal cancer, which can provide a basis for the evaluation and treatment of patients, and are worthy of widespread clinical application.